Mapping shrub cover in grasslands with an object-based approach and investigating the connection to topo-edaphic factors. Issue 27 (13th December 2022) - Soubry, Irini; Robinov, L.; Chu, T.; Guo, X.
Abstract: Shrubs are important for grasslands; however, shrub encroachment has threatened the integrity of grasslands worldwide. Understanding shrub extent and local effects on encroachment can prioritize management. Studies that map low stature shrubs using an object-based approach in large areas of northern grasslands are limited. This study i) locates shrubs with an object-based approach using 30 cm colour-infrared aerial imagery and Support Vector Machine classification; and ii) investigates shrub distribution by topo-edaphic factors in the native fescue grasslands of the West Block in Cypress Hills Interprovincial Park, Saskatchewan, Canada. The overall accuracy of detected shrubs was above 92%. Loam flat regions, North-facing slopes, and areas with 0% to 25% slope rise are connected to high shrub cover and relate to soil moisture. Shrub presence is high closer to watercourse lines and waterbodies, and low closer to wetlands. This research can apply to other shrub encroached areas to facilitate shrub management worldwide.